Influence of the Cavity-Depth/light Tip-Material Distance on the Degree of Conversion and Physical Properties of a Nanohybrid Resin Composite Employing the Incremental Technique - Roque Trujillo, Javier F.; Murillo-Gómez, Fabián (Odovtos - International Journal of Dental Sciences, 2025)
Evaluate the influence of different cavity depth and consequent light-tip/material distance, on the degree of conversion, biaxial flexural strength and microhardness of a nanohybrid resin-composite (top/bottom), employing the incremental technique. Quadrangular samples (4x4mm) with thickness variations (cavity-depth simulation: 2, 4, and 6 mm; n=10) were made using a nanohybrid resin-composite (Forma, A3, Ultradent) employing the incremental technique. Vickers Microhardness and degree of conversion were assessed on top/bottom surfaces. Biaxial flexural strength was tested on resin-composite discs (8.5mm diameter, 2mm thick) using 3D-printed molds (vertically stacked). Microhardness and Degree of conversion data were analyzed employing 2-way/ANOVA, Biaxial flexural strength with 1-way/ANOVA.For microhardness, “distance” factor plus “surface/distance” interaction resulted statistically significant (p<0.05). The 2 mm group, followed by the 4 mm group, showed the highest results (99.41±52.23 and 84.1±15.74 VHN), while the 6 mm group had the lowest (68.60±18.69 VHN), with lower values observed on the bottom surfaces for the latter group only. Biaxial flexural strength data showed no significant differences among groups. Degree of conversion was significantly higher at the top surfaces compared to the bottom surfaces (top: 47.74±9.67%; bottom: 21.93±8.57%). At 2 and 4 mm distance, polymerization quality remained adequate (top/bottom surfaces). A 6 mm distance produced lower quality polymerization, mainly on the bottom surfaces. In such scenario, an additional photopolymerization cycle may be desirable. The current outcomes may be related only to the conditions (RBC, distances and LCU) employed in this study.